Navigating Financial Landscapes A Qualitative Study On Cash Flow Volatility, Intellectual Capital, Human Capital, And Tax Compliance Awareness - Sonya Imelda Patrecia; Muhammad Arif Rahman (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This study aims to investigate the dynamics between cash flow volatility, intellectual capital, human capital, and tax compliance awareness within financial landscapes. The research model incorporates these key components to comprehend their interplay and implications. A purposive sampling technique was employed to select participants from diverse financial sectors. Data were collected through in-depth interviews and analyzed thematically to extract patterns and insights. The findings reveal intricate relationships among cash flow volatility, intellectual capital management, human capital development, and tax compliance awareness. Notably, organizations with robust intellectual and human capital frameworks demonstrate better adaptability to cash flow fluctuations and exhibit higher levels of tax compliance awareness. This study contributes to a deeper understanding of the multifaceted factors influencing financial dynamics and highlights the importance of strategic resource management in fostering financial resilience and compliance.